Soils with vertic properties in Kamennaya Steppe - N. B. Khitrov; Yu. I. Cheverdin; N. P. Chizhikova; L. V. Rogovneva (Бюллетень Почвенного института им. В.В. Докучаева, 2013)
The most spread are soils with vertic properties at the territory of Kamennaya Steppe (Voronezh region, Talovsky district) being confined to four landscape positions within 11 different soil combinations derived from clayey or two-layered heavy loam-clayey parent materials. These soils have developed: (A) on bottoms of deep and closed depressions covered by spotted soil combinations in flat watersheds; (B) on some depression bottoms in spotted combinations without solonetzic soils; (C) in different relief elements occupied by chernozemic hydromorphic solonetz complexes and (D) in concave (in long and cross directions) relief elements in the topolithomosaic composition confined to exposed re-deposition products of Dnieper moraine on the slope of Talovaya narrow. Occupying only 0.2% from the total area of agro-forest landscapes, the vertic soils can account for 0.7% to 15% within a separate soil combination and reveal a great diversity. The latter is associated with vertic properties developed together with features of gleying and quasi-gleying, accumulation of calcium carbonates and, on the contrary, clay illuviation against the background of calcium carbonate leaching, solonetz process, salinization, humus formation and the topsoil eluviations. Such a diversity may be adequately reflected both in the soil classification of Russia and in WRB.